NOURISHMENT OR NEGLECT: UNDERSTANDING THE INFLUENCE OF DIET ON THE SURGE OF GASTRIC CANCER IN PAKISTAN - Berkha Rani, (Journal of Ayub Medical College Abbottabad, 2024)
Gastric cancer, a malignant tumour originating in the stomach, has become a pressing health concern in Pakistan. The country has witnessed a significant rise in gastric cancer cases over the past few decades, prompting researchers and healthcare professionals to investigate the potential role of diet in this alarming trend. As the saying goes, "You are what you eat," and it is crucial to examine the dietary patterns prevalent in Pakistan and their impact on gastric cancer development. Pakistan, known for its rich and diverse culinary traditions, offers a wide array of food choices. However, the dietary landscape has undergone notable changes due to urbanization, globalization, and shifting lifestyle patterns. Traditional, homemade meals are increasingly being replaced by convenient, processed, and fast-food options. This transition has resulted in a substantial increase in the consumption of calorie-dense, nutrient-poor foods that are often high in fat, sugar, and salt. One dietary factor that has garnered attention about gastric cancer is the consumption of preserved and salted foods. Pakistani cuisine is known for its love of pickles, cured meats, and salted fish, all of which contain high levels of sodium and nitrates. Prolonged exposure to these preservatives may contribute to the development of gastric cancer by causing damage to the gastric mucosa and promoting inflammation. Studies have suggested a positive association between the intake of preserved and salted foods and the risk of gastric cancer, highlighting the need for moderation and awareness. Another aspect of the Pakistani diet that requires scrutiny is the low intake of fruits and vegetables. These plant-based foods are rich in vitamins, minerals, fibre, and antioxidants, all of which play a vital role in maintaining a healthy digestive system and protecting against various cancers, including gastric cancer. However, the modern dietary shift has led to a decrease in the consumption of fresh fruits and vegetables, depriving individuals of their potential protective effects. Encouraging the inclusion of a variety of fruits and vegetables in daily meals can help mitigate the risk of gastric cancer and promote overall health and well-being. Furthermore, the widespread consumption of red and processed meats in Pakistan is a cause for concern. High intake of these meats has been associated with an increased risk of gastric cancer due to their potential carcinogenic properties. Chemical compounds formed during the processing and cooking of meats, such as heterocyclic amines and polycyclic aromatic hydrocarbons, may contribute to gastric cancer development. Encouraging a reduction in the consumption of red and processed meats, as well as promoting alternative protein sources, can be a crucial step in curbing the surge of gastric cancer cases. It is important to acknowledge that diet is just one component of a multifaceted disease like gastric cancer. Other factors, such as genetic predisposition, environmental exposures, and lifestyle choices, also contribute to its development. Nonetheless, understanding the influence of diet and its potential impact on gastric cancer in Pakistan is a vital step towards formulating targeted preventive strategies. Educational campaigns and public health initiatives can play a pivotal role in raising awareness about the relationship between diet and gastric cancer. Promoting healthy eating habits, advocating for the consumption of fresh and minimally processed foods, and emphasizing the importance of a balanced diet can empower individuals to make informed dietary choices. Collaborative efforts between healthcare professionals, policymakers, and the food industry are necessary to create an environment that supports and encourages healthier dietary patterns. In conclusion, the surge of gastric cancer in Pakistan demands attention and action. By comprehending the influence of diet on gastric cancer development and adopting preventive measures, it is possible to address this growing health concern. Encouraging a shift towards a diet rich in fruits, vegetables, and whole grains, while reducing the consumption of preserved and salted foods, red and processed meats, can contribute to a healthier population and a decline in gastric cancer incidence. Nourishment through a balanced diet should be prioritized to combat neglect and pave the way for a healthier future.